Importance of drinking - water for human health in large cities - Архіпова, Г.І.; Мудрак, Т.О.; Завертана, Д.В.; Остапець, О.В. (Proceedings of National Aviation University (archive), 2010)
Concidered are the main special features of potable water in the large town, where the main source of its supplingis the urban waterworks.